Being and Dwelling through Tourism : An anthropological perspective - Palmer, Catherine (London : Taylor and Francis, 2018)
"Much of the existing literature seeks to make sense of tourism based on singular approaches such as visuality, identity, mobility, performance and globalised consumption. What is missing, however, is an overarching framework within which these valuable approaches can be located. This book offers one such framework using the concept of dwelling taken from Heidegger and Ingold as the starting point from which to consider the interrelatedness of being, dwelling and tourism.The anthropological focus at the core of the book is infused with multidisciplinary perspectives that draw on a variety of subjects including philosophy, material cultural studies and cultural geography. The main themes include sensuous, material, architectural and earthly dwelling and each chapter features a discussion of the unifying theoretical framework for each theme, followed by an illustrative focus on specific aspects of tourism. This theoretically substantive book will be of interest to anyone involved with tourism research from a wide range of disciplines including anthropology, sociology, geography, cultural studies, leisure studies and tourist studies."--Provided by publisher.
chapter 1 Being and dwelling / Catherine Palmer -- chapter 2 Sensuous dwelling / Catherine Palmer -- chapter 3 Material dwelling / Catherine Palmer -- chapter 4 Architectural dwelling / Catherine Palmer -- chapter 5 Earthly dwelling / Catherine Palmer -- chapter 6 Being, dwelling and thinking / Catherine Palmer.
Keywords: Anthropology; Cultural geography; Culture and tourism; Human geography; Tourism -- Social aspects; Tourism